STATUS KADAR TROMBOSIT AKIBAT PAPARAN PESTISIDA PADA PETANI - Nur Vita Purwaningsih; Tri Ade Saputro; Ellies Tunjung SM; Rahma Widyastuti; Ainutajriani Ainutajriani; Baterun Kunsah (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Pesticides are substances or chemicals used in agriculture, forestry, horticulture and public land to increase crop yields. Up to now, pesticides are the main choice for farmers to protect plants from the influence of various plant-disturbing organisms. Exposure to pesticides on the body can have a negative impact on components in the body, including blood. Pesticides can be estimated as one of the factors that affect the blood profile, one of which is thrombocyte. The purpose of this study was to determine the description of platelet levels in farmers exposed to pesticides in Trece Village, Mojokerto Regency. This research was a descriptive study with an observational design. This research was conducted by checking the thrombocyte count of farmers in Trece Village, Mojokerto Regency, which was carried out automatically using a hematology analyzer. The results showed that the farmers of Trece Village, Mojokerto Regency who had normal platelet levels were 26 people with a percentage of 87% and 4 people with a low percentage of 13%. The conclusion in this study is that not all reductions in thrombocyte levels are due to exposure to pesticides and not always those who exposed to pesticides have low thrombocyte level.